Identitas Sosial Remaja Rentan dalam Konteks Kemiskinan Perkotaan di Makassar - Firdaus, Faradillah (HUMAN: South Asian Journal of Social Studies, 2025)
Abstract. This study aims to explore the construction of social identity among vulnerable youth in the context of urban poverty in Makassar through in-depth qualitative analysis. Using a phenomenological approach with 12 participants aged 16-24 years living in poor urban areas, data were collected through in-depth interviews and participant observation. Data analysis used interpretative phenomenological analysis to understand lived experiences and meaning-making processes. Results revealed three major themes: identity negotiation through resistance strategies, collective identity as a protective mechanism, and cultural resources as identity capital. Participants actively constructed positive social identities despite structural constraints through reframing poverty narratives, emphasizing community solidarity, and drawing on local cultural values. The findings challenge deficit-based perspectives of poor youth and highlight their agency in identity construction. This study contributes to understanding how vulnerable youth navigate social stigma while maintaining positive self-regard through creative identity work and cultural resilience.Keywords: social identity; vulnerable youth; urban poverty; qualitative research; cultural resilience